2021
DOI: 10.3389/fpubh.2021.669057
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Anxiety, Stress and Resilience During the COVID-19 Pandemic: Evaluating the Vulnerability of Academic Professionals in Mexico Through the Adapted COVID-19 Stress Scales

Abstract: To mitigate the COVID-19 infection, many world governments endorsed the cessation of non-essential activities, such as the school attendance, forcing a shift of the teaching model to the virtual classroom. From this shift, several changes in the teaching paradigm derived, in addition to the COVID-19 pandemic, which could have an impact in academic professional's mental health. In the present work we show the application of a modified version of the adapted COVID-19 stress scales (ACSS) which also included teac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
10
0
5
Order By: Relevance
“…Given the extent COVID-19 pandemic has affected the country (2,17,23) and how recent advances in technology have moved forward interconnectivity (23)(24)(25), we opted to use electronic means to implement our questionnaire, as this becomes both a permissible way to distribute to the general population and to follow preventive measures such as social distancing. As earlier stated, we used direct email invitation and posting links to the questionnaire in popular social media platforms used by the public.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the extent COVID-19 pandemic has affected the country (2,17,23) and how recent advances in technology have moved forward interconnectivity (23)(24)(25), we opted to use electronic means to implement our questionnaire, as this becomes both a permissible way to distribute to the general population and to follow preventive measures such as social distancing. As earlier stated, we used direct email invitation and posting links to the questionnaire in popular social media platforms used by the public.…”
Section: Resultsmentioning
confidence: 99%
“…We could consider this as a limitation as it is unsupervised in-person, particularly during the quarantine, remote evaluations provide a safe alternative, albeit relying on the inclination of participant to answer. Currently, online surveys have been used by several groups, particularly in COVID-19 pandemic, to gather public or particular selected group information (17,23,(35)(36)(37). As stated elsewhere in the manuscript, we distributed the questionnaire either by direct email invitation (we further asked participants to send to other colleagues or acquaintances the link to the questionnaire) or by popular social media platforms.…”
Section: Covid-19 Vaccine Hesitancy In Mexicomentioning
confidence: 99%
“…Interestingly, we also see that both young (18 to 34 years) and mid-age (35 to 54 years) parents present relevancy. Although older active adults are most likely concerned about child infections, many studies have shown that the initial most-at-risk group was actually the older adults, particularly those with comorbidities [ 30 , 38 , 43 , 44 , 45 , 46 ]. Therefore, it is most likely that older active adults are currently more worried about their own health.…”
Section: Discussionmentioning
confidence: 99%
“…The present study derives from the application of the online COVID-19 Vaccine Acceptance & Hesitancy Questionnaire, or COV-AHQ (Cronbach’s alpha > 0.8) [ 27 ], which was designed based on the initial and Adapted COVID-19 Stress Scales (CSS and ACSS) [ 28 , 29 , 30 ] and the Vaccine Hesitancy Scales (VHS) [ 22 ]. For the present study, we took into consideration only the subpopulation of participants with the criteria of answering yes to having children.…”
Section: Methodsmentioning
confidence: 99%
“…Authorities worldwide have decreed that students at all levels incorporate remote education from home. As part of this new reality, teachers have had to incorporate technological tools that have raised stress levels in those who did not use multimedia tools regularly [ 2 ]. Some higher education institutions still maintain this remote arrangement, while others have gradually reopened.…”
Section: Introductionmentioning
confidence: 99%